Management Specialists' Training Social Schemes: World Experience and Russian Specificity - М А Ignatskaya; G А Kulikovskaya (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2010)
The article offers the analysis of the issues related to the social administration of professional management personnel training which have become particularly complicated over the past two decades. Social schemes, conditions and factors of management are shown to be closely interconnected with the characteristics of human capital as the basis for social, economic and cultural development of the contemporary society. World experience and Russian specificity in the sphere of human resource management specialists' training are analyzed.